Routine Echocardiography is not Required in Neonates with Arterial Ischemic Stroke - Bhagat, Indira; Sarkar, Rohan; Bapuraj, Jayapalli R.; Sarkar, Subrata (American Journal of Perinatology, 2024)
Objective Current guidelines suggest routine echocardiography (ECHO) in the acute phase to exclude a cardiac source for neonatal arterial ischemic stroke (NAIS). However, the commonly assumed embolic origin from a cardiac source for NAIS is challenged and the need for ECHO in NAIS remains questionable, especially during the era of standard fetal anomaly scanning. Our hypothesis is that any complex cardiac defects potentially causing NAIS would likely be detected during routine prenatal scans, thus possibly making routine postnatal ECHO redundant. This study aimed to determine the prevalence of significant cardiac risk factors and evaluate the necessity of routine postnatal ECHO in NAIS during the routine use of prenatal fetal sonography.Study Design Retrospective review of 54 infants diagnosed with NAIS via brain magnetic resonance imaging who underwent an ECHO evaluation during the acute period to exclude potential cardiac origins for NAIS.Results Postnatal ECHO revealed no intracardiac thrombus or vegetation, and only identified structural heart anomalies in three (5%) infants. Interestingly, these three cases had already been diagnosed with syndromic conditions or chromosomal malformations prenatally. In the remaining infants, postnatal ECHO was either normal or showed minor abnormalities unlikely to have contributed to the stroke. The detection rates of complex cardiac anomalies from prenatal scans and postnatal ECHO were statistically similar (p = 0.617).Conclusion The probability of ECHO to exclude cardiac sources for NAIS is so low that in the era of standard fetal anomaly scanning, routine postnatal ECHO may not be necessary for all NAIS infants, except when chromosomal malformations are detected.Key Points
Keywords: neonatal arterial ischemic stroke; echocardiography; prenatal fetal scanning; chromosomal malformations